Marine Reservoir Correction for American Samoa Using U-series and AMS Dated Corals. Issue 4 (4th August 2016) - Clark, Jeffrey T; Quintus, Seth; Weisler, Marshall I; Pierre, Emma St; Nothdurft, Luke; Feng, Yuexing; Hua, Quan
Abstract: Radiocarbon dating of marine samples requires a local marine reservoir correction, or ΔR value, for accurate age calibrations. For the Samoan Archipelago in the central Pacific, ΔR values have been proposed previously, but, unlike some Polynesian archipelagoes, ΔR values seem not to vary spatially and temporally. Here, we demonstrate such variability by reporting a ΔR of –101±72 ΔR for the Manu'a Group—the eastern-most islands in the archipelago—for the colonization period. This value is based on accelerator mass spectrometry (AMS) 14 C and uranium-thorium (U-Th) series dating of individual coral branches from pre-2300 cal BP archaeological contexts. This figure differs from the previously proposed modern ΔR of 28±26 yr derived from dated historic, pre-1950, shell samples from the western islands of Samoa. Consequently, we recommend using the ΔR of –101±72 yr for the 1st millennium BC in Manu'a, and 28±26 yr for calibrating dates within the 2nd millennium AD in the western islands (Savai'i to Tutuila). Until more data from across the archipelago and from throughout the entire culture-historical sequence document ΔR variability, we recommend that researchers use both of these ΔR values to evaluate how the dates of marine-derived samples compare with AMS dates on identified, short-lived wood charcoal.